Предмет: Алгебра, автор: OliverSykes18

ПОМОГИТЕ С 4 ЗАДАНИЕМ ПОЖАЛУЙСТА!

Приложения:

Ответы

Автор ответа: inblu
0
(frac{m}{m-6}- frac{2m}{m^2-12m+36})* frac{36-m^2}{m-8}+ frac{12m}{m-6}= \ =(frac{m}{m-6}- frac{2m}{(m-6)^2})* frac{36-m^2}{m-8}+ frac{12m}{m-6}=frac{m(m-6)-2m}{(m-6)^2}* frac{6^2-m^2}{m-8}+ frac{12m}{m-6}= \ =frac{m^2-6m-2m}{(m-6)^2}* frac{(6-m)(6+m)}{m-8}+ frac{12m}{m-6}=frac{m^2-8m}{(m-6)^2}* frac{-(m-6)(6+m)}{m-8}+ frac{12m}{m-6}= \ =-frac{m(m-8)}{(m-6)^2}* frac{(m-6)(6+m)}{m-8}+ frac{12m}{m-6}=-frac{m(6+m)}{m-6}+ frac{12m}{m-6}
frac{-(6m+m^2)+12m}{m-6}= frac{12m-6m-m^2}{m-6}= frac{6m-m^2}{m-6}= frac{m(6-m)}{m-6}= frac{-m(m-6)}{m-6}=-m
Похожие вопросы
Предмет: Алгебра, автор: ksssery7